THE EFFECT OF GREEN HUMAN RESOURCE MANAGEMENT ON CORPORATE ENVIROMENTAL PERFORMANCE AT PERUMDA TIRTA PASE, NORTH ACEH WITH EMPLOYEE ENVIROMENTAL COMMITMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR FOR THE ENVIRONMENT AS INTERVENING VARIABLES - Imran; Faisal Matriadi; Darmawati Muchtar; Marbawi; Ibrahim Qamarius; Nur Faliza (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study analyzes the effect of Green Human Resource Management (GHRM) on Corporate Environmental Performance (CEP). Additionally, this study examines the mediating roles of Employee Environmental Commitment (EEC) and Organizational Citizenship Behavior for the Environment (OCBE). The study used a sample of 120 employees from Perumda Tirta Pase North Aceh. Data analysis was conducted using path analysis with Structural Equation Modeling (SEM) through AMOS software. The results show that GHRM has a positive but insignificant effect on CEP. GHRM positively and significantly affects both EEC and OCBE. EEC has a positive and significant effect on CEP, whereas OCBE has a positive but insignificant effect on CEP. The mediation test results indicated that EEC could not mediate the effect of GHRM on CEP because the direct effect of GHRM on CEP was not significant. Similarly, OCBE cannot mediate the effect of GHRM on CEP for the same reason.